Rede Globo e territorialidades : controle e sobrevivência sob a ótica do paradigma da complexidade - Mantovaneli, Wagner Piassaroli (2015)
This research aims to investigate the relationship between Rede Globo and control society context. To this end, we describe a history of Rede Globo behavioral strategies in the political and economic framework so that we can place it in the desired context without, however, forgetting the extensive historical process that leads to such a relationship. We will study this object and its relationship to the context from a perspective of the social, which is the political economy. From definition proposed by Vincent Mosco, we decided to analyze the social in terms of mutual constitution of the social reproduction (economy) and the social control (policy), able to take us to a conception of a totality dinamized by historical process. From the beginning to the present day where Marinho family is still present, it is evident its role during the Brazilian industrialization process in the consolidation of a modern Brazilian society related to the context of overall survival relations. The national communication system that would help to aggregate the country would be, increasingly, consistent with the worldwide system of communication, led by the United States, especially. In this conjunction, we come to the society of control, consisting of global and local territoriality in recursive relationship. To study this process we could not find ourselves comfortable before knowing how to deal with the complex web involving the social. Dealing with this complexity is, first, to know the possibilities that knowledge has to produce a consistent thought with the multiple relations organized in certain methodological system. We found in Morin’s complexity paradigm a way to understand the knowledge and make it a good tool to the understanding of what is woven together in society. Seeing our object - Globo - as a major player in the great game of control society involves thinking the territorial systems in which it negotiates its power, producing and being produced at the same time by social forces. Thinking of so many relations and relations of relations brings us to surrender to a paradigm of complexity, that is, a knowledge capable of dealing with a reality made up of order and chaos in mutual constitution.